Surface coated cutting tools
Patent Information
- Application Number
- JP2025057890
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0008】 前記表面被覆切削工具は、オーステナイト系ステンレス鋼、析出硬化系ステンレス鋼、Ti合金、Ni合金等の難削材の切削加工であっても、優れた耐久性を有する。
Smart Images

Figure 2026165482000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a surface-coated cutting tool (hereinafter sometimes referred to as a coated tool). [Background technology]
[0002] Conventionally, coated tools have been known in which a coating layer is formed on the surface of a substrate such as a tungsten carbide (hereinafter referred to as WC)-based cemented carbide to improve the lifespan of cutting tools. Furthermore, various proposals have been made regarding the composition and structure of the coating layer in order to further improve the cutting performance of coated tools.
[0003] For example, Patent Document 1 describes a coating layer made of Ti 1-x Al x A first nanolayer with N(0.35≦x≦0.70) and Ti 1-y Si y A coated tool is described which includes a nanomultilayer with alternating layers of a second nanolayer having N(0.12≦y≦0.25), where the first nanolayer and the second nanolayer (10) form an alternating stack, and the average layer thickness of the alternating stack is 7 nm or less. The coated tool is said to have excellent resistance to crater wear and flank wear.
[0004] Furthermore, for example, Patent Document 2 describes a coated tool in which the coating layer consists of one or more metallic elements selected from groups 4-6 of the periodic table, Al, and B, and one or more nonmetallic elements selected from Si and C, N, and O, and has a columnar structure with an fcc structure, the crystal grains in the columnar structure have a multilayer structure consisting of multiple layers with different Si content, at least regions where crystal lattice fringes are continuous exist in the boundary regions between the layers, the thickness T (nm) of each layer is 0.1 ≤ T ≤ 100, Si exists as crystalline phases of α-type Si3N4 and β-type Si3N4, and when the peak intensity of the α-type Si3N4 by Raman spectroscopy is Iα and the peak intensity of the β-type Si3N4 is Iβ, Iβ / Iα < 1.0, and the lattice constant of the (200) plane by X-ray diffraction is 0.4100 to 0.4300 nm, and this coated tool is said to have stability and long tool life even in dry high-efficiency cutting and strong intermittent cutting.
Prior Art Documents
Patent Documents
[0005]
Patent Document 1
Patent Document 2
SUMMARY OF THE INVENTION
Problems to be Solved by the Invention
[0006] The present invention has been made in view of the foregoing circumstances and the foregoing proposals, and an object thereof is to provide a surface-coated cutting tool that has excellent durability even in cutting processing of difficult-to-cut materials such as austenitic stainless steel, precipitation hardening stainless steel, Ti alloys, and Ni alloys.
Means for Solving the Problems
[0007] A surface-coated cutting tool according to an embodiment of the present invention comprises: a substrate and a coating layer, the coating layer includes a lower layer and an upper layer, the lower layer has an A layer, and the upper layer is a laminate in which a B layer on the substrate side and an A layer on the B layer are taken as a lamination unit, the upper layer and the lower layer each have an average thickness of 0.5 to 3.5 μm, and the total average thickness of both layers is 1.0 to 5.0 μm, The A layer is composed of a first compound represented by the formula: Al a Ti 1-a-b X b Y c N (X is Ta and / or Nb, Y is Si and / or B, and on average 0.40<a<0.70, 0.00≦b<0.20, 0.00≦c<0.05) The B layer is composed of a compound represented by the formula: Ti 1-d-e Si d Z eN (Z is at least one selected from the group consisting of Ta, Nb, and B, with average values of 0.15 < d ≤ 0.40 and 0.00 ≤ e ≤ 0.20 respectively), and is composed of a second compound represented by Among the crystal grains crossing the interface between the lower layer and the upper layer in the longitudinal cross section of the coating layer, the proportion of crystal grains that have epitaxially grown from the lower layer to the upper layer is 70% or more. When the average thickness of the upper layer is defined as L, and the average value of the protrusion amount of the epitaxially grown crystal grains from the interface toward the upper layer side is defined as H (μm), 0.05 × L (μm) < H < 0.50 (μm) is satisfied. Effects of the Invention
[0008] The surface-coated cutting tool has excellent durability even in the cutting of difficult-to-cut materials such as austenitic stainless steel, precipitation hardening stainless steel, Ti alloy, and Ni alloy. Brief Description of the Drawings
[0009] [Figure 1] It is a schematic diagram showing an example of a longitudinal cross section of a surface-coated cutting tool according to an embodiment of the present invention. [Figure 2] It is a schematic diagram illustrating the morphology of crystal grains for explaining epitaxial growth at the interface between the lower layer and the upper layer. Modes for Carrying Out the Invention
[0010] The present inventors conducted intensive studies to obtain a surface-coated cutting tool that has durability even in the cutting of difficult-to-cut materials such as stainless steel, Ti alloy, and Ni alloy (hereinafter sometimes collectively referred to as difficult-to-cut materials), and obtained the following findings. 1. As a result of studying known coating layers, the following matters were recognized.
[0011] (1) Causes of coating layer damage that occurs during cutting of difficult-to-cut materials include a decrease in the hardness of the coating layer due to the elevated temperature of the cutting edge, embrittlement due to oxidation of the coating layer, and welding. (2) In order to provide a coating layer with excellent heat resistance, the coating layer is made of AlCrN. However, in particular when cutting austenitic stainless steel, the Cr contained in the workpiece and the Cr contained in the coating layer mutually diffuse, causing the weld to adhere more firmly and accelerating weld wear.
[0012] (3) Therefore, it is necessary to have a coating layer that does not contain Cr, such as AlCrN, and has excellent heat resistance. (4) Examples of such compounds include AlTiN and TiSiN, but AlTiN has poor heat resistance, and TiSiN has excellent heat resistance but poor adhesion to the substrate and AlTiN layer. (5) Furthermore, it is possible to improve the heat resistance of AlTiN by adding Si and B, but the addition of these elements promotes the precipitation of hexagonal crystals and refines the crystal grains, so there are limitations on the amount that can be added.
[0013] 2. Therefore, the inventors conducted thorough research and found that, If the compound is obtained by further adding Ta and Nb to AlTiN, which contains the aforementioned compounds Si and B, then hexagonal crystal precipitation can be suppressed, improving the heat resistance of the coating layer, and appropriately refining the crystal grains. Furthermore, by adding Ta, Nb, or B to TiSiN, it is possible to improve heat resistance and oxidation resistance. Furthermore, by alternately stacking coating layers containing these compounds at a thickness of nanometers, it is possible to dramatically improve the heat resistance of the coating layers. In addition, by adding Ta, Nb, etc. to the AlTiN compound with Si and B added for use in alternating lamination as the lower layer, it is possible to improve the adhesion between the substrate and the coating layer, and furthermore, the amount of damage when the coating layer is welded and detached can be reduced. This invention was derived from the insights gained.
[0014] The following describes a surface-coated cutting tool according to an embodiment of the present invention. In this specification and in the claims, when a numerical range is expressed as "L~M" (where L and M are both numerical values), it is synonymous with "greater than or equal to L and less than or equal to M," and the range includes both an upper limit (M) and a lower limit (L). When a unit is specified only for the upper limit, the units of the upper limit (M) and the lower limit (L) are the same. The average refers to the arithmetic mean.
[0015] Furthermore, the term "surface of the substrate" as used in this specification and in the claims refers to the average line (straight line) of the roughness curve at the interface between the coating layer closest to the substrate surface and the substrate, calculated arithmetically. According to this method for calculating the average line, even if the substrate has a curved surface, if the tool diameter (substrate diameter) is sufficiently large relative to the thickness of the coating layer, the interface between the coating layer and the substrate can be treated as a plane, and thus the surface of the substrate can be determined in the same manner. Further details will be described later. Furthermore, a longitudinal section refers to a cross-section perpendicular to the surface of the substrate, assuming that minute irregularities on the substrate surface do not exist and treating it as a flat surface.
[0016] Figure 1 shows a schematic diagram illustrating an example of a longitudinal section of a surface-coated cutting tool according to an embodiment of the present invention. According to this diagram, the coating layer (2) has a lower layer (3) as the layer closest to the substrate (1), and this lower layer (3) is an A layer (5) composed of a first compound, AlTiXYN (where X is Ta and / or Nb, and Y is Si and / or B). In contact with the lower layer (3), there is an upper layer (4) which contains multiple stacking units (7) of an A layer (5) where the substrate side is composed of a second compound, TiSiZN (where Z is at least one selected from the group consisting of Ta, Nb, and B), and the cutting tool surface side is composed of the first compound.
[0017] Furthermore, a base layer may be selectively provided between the substrate (1) and the lower layer (3), and a surface layer may be selectively provided on the surface of the upper layer (the base layer and surface layer are not shown in the figure). The lower layer (3), upper layer (4), base layer, and surface layer then constitute the covering layer (2). Note that there are also stacking units in the parts indicated by the vertically aligned "···" in Figure 1. Each of these layers will be explained below in order.
[0018] 1. Coating layer The coating layer includes a lower layer and an upper layer. The lower layer is an A layer composed of a first compound, and the upper layer is a laminate in which a lamination unit (the B layer is located on the substrate side) consisting of the A layer composed of the first compound and a B layer composed of a second compound is laminated. Hereinafter, description will be given in order.
[0019] (1) Lower layer The lower layer is formed in contact with the surface of the substrate or the underlayer.
[0020] 1) Average thickness The average thickness of the lower layer is 0.5 to 3.5 μm. The reason for setting the average thickness of the lower layer within this range is that if the average thickness is less than 0.5 μm, the adhesion between the coating layer and the substrate is not sufficient, while if the average thickness is greater than 3.5 μm, the internal strain in the lower layer increases, making the lower layer prone to fracture.
[0021] 2) Average composition The lower layer is represented by the formula: Al 1-a-b Ti a X b Y c N (X is Ta and / or Nb, Y is Si and / or B, and on average 0.40<a<0.70, 0<b<0.20, 0.00≦c<0.05) is a layer composed of the first compound represented by the above. The reason why the above composition is preferred in the first compound is as follows.
[0022] · Regarding the a value (atomic ratio) indicating the content ratio of Al When the a value is less than 0.40, high-temperature hardness and high-temperature oxidation resistance decrease. On the other hand, when it exceeds 0.70, the lower layer becomes brittle due to the precipitation of hexagonal crystals, and sufficient wear resistance cannot be obtained.
[0023] · Regarding the b value (atomic ratio) indicating the content ratio of X The X component is essentially contained to suppress the precipitation of hexagonal crystals in the first compound, but when the b value is 0.20 or more, the hardness decreases, so that sufficient wear resistance cannot be obtained.
[0024] Regarding the c-value (atomic ratio) indicating the content ratio of Y It is more preferable that the Y component is contained in the first compound to improve heat resistance. When the c-value is 0.05 or more, sufficient adhesion and heat resistance cannot be obtained due to excessive refinement of the crystal grain size and precipitation of a hexagonal crystal system.
[0025] 2. Upper layer The upper layer is a laminate having a lamination unit consisting of a B-layer on the substrate side (details will be described later) and an A-layer having the same composition as the A-layer constituting the lower layer on the tool surface side. In principle, the layer on the tool surface of the upper layer is the B-layer, but it may be the A-layer.
[0026] As shown in Figure 2, the crystal grains in the upper layer include those (10) that are epitaxially grown from the lower layer and those (11) that are not affected by the lower layer and are not epitaxially grown. The grains epitaxially grown from the lower layer have a portion (region) satisfying the A-layer component and a portion (region) satisfying the B-layer component within the same crystal, and this same crystal constitutes the lamination unit.
[0027] 1) Average thickness The average thickness of the upper layer is 0.5 to 3.5 μm. The reason is that if the average thickness is less than 0.5 μm, the weld resistance of the coating layer is not sufficient, and if it exceeds 3.5 μm, the internal strain of the upper layer increases, making the upper layer prone to fracture.
[0028] 3) Average composition The A-layer is composed of the first compound having the same average composition as the A-layer constituting the lower layer. The B-layer is composed of the second compound having the following average composition. That is, the average composition is represented by the formula: Ti 1-d-e Si d Z e N (Z is at least one selected from the group consisting of Ta, Nb, and B, and on average, 0.15<d≤0.40 and 0.00≤e≤0.20, respectively).
[0029] ·Regarding the d value (atomic ratio) indicating the content ratio of Si When the d value is 0.15 or less, sufficient improvement in heat resistance and mechanical properties cannot be obtained. On the other hand, when the d value exceeds 0.40, sufficient toughness of the coating layer cannot be obtained due to excessive refinement of crystal grain size and high compressive residual stress.
[0030] ·Regarding the e value (atomic ratio) indicating the content ratio of Z The Z component is essentially contained in the second compound to improve heat resistance and oxidation resistance, but when the e value exceeds 0.20, sufficient adhesion between the upper layer and the lower layer cannot be obtained due to the application of excessive compressive residual stress.
[0031] 3) Epitaxial growth The proportion of crystal grains that have epitaxially grown from the lower layer to the upper layer is 70% or more. The reason is that if the proportion is less than 70%, sufficient adhesion of the upper layer cannot be obtained, the upper layer will peel off at an early stage, and sufficient wear resistance cannot be obtained. The upper limit of this proportion may be 100%. When it is 100%, the highest adhesion can be obtained.
[0032] When the average thickness of the upper layer is defined as L, and the average value of the protrusion amount from the interface to the surface of the portion where the crystal grains are epitaxially grown is defined as H, the relation 0.05L(μm) < H < 0.50(μm) is satisfied. The reason is that when H is 0.05L(μm) or less, sufficient adhesion between the lower layer and the upper layer cannot be obtained, and when H is 0.50 μm or more, the hardness is lowered, and sufficient wear resistance cannot be obtained. The method for confirming the epitaxially grown portion will be described later.
[0033] (5) Other layers (5-1) Optionally present layer Although the aforementioned problems can be sufficiently solved with only the lower layer and the upper layer, in addition to these layers, an underlayer may be optionally provided between the substrate and the lower layer, and / or a surface layer may be optionally provided on the tool surface side of the upper layer.
[0034] A Underlayer While the aforementioned objectives can be fully achieved with just the lower and upper layers, a sub-layer may be included between the lower layer and the base. Examples of the underlayer include at least one layer composed of TiN and at least one layer composed of CrN, with an average thickness of 0.1 to 1.0 μm. When the average thickness is within this range, the adhesion between the underlayer and the substrate is further improved.
[0035] I. Surface layer The upper layer can be exemplified by a TiN layer. Since the TiN layer has a golden hue, it can be used as an identification layer to determine, for example, whether a coated tool is unused or used by observing the change in color on the tool's surface. The average thickness of this TiN layer, which serves as the identification layer, can be, for example, 0.1 to 1.0 μm.
[0036] (5-2) Layers consisting of compounds that may occur by chance In this embodiment, the film is formed so that there are no layers other than the lower layer, upper layer, underlayer, and surface layer. However, when changing the type of layer to be formed, pressure changes and temperature fluctuations may occur unintentionally, and (unintentionally) other compounds may be formed by chance, resulting in the existence of layers containing other compounds. These layers are called layers that may occur by chance. Furthermore, "the P layer contains X" and "the Q layer consists of Y" indicate that the P layer may contain other compounds that occur by chance other than X, and the Q layer may contain other compounds that occur by chance other than Y, respectively. Also, "the R layer contains the Z layer" indicates that there may be layers other than the Z layer that may occur by chance.
[0037] 3.Base (1)Material The substrate used in this embodiment can be any of the conventionally known substrate materials, as long as it does not hinder the achievement of the aforementioned objectives. For example, it is preferable to use any of the following: WC-based cemented carbide (including those containing WC and Co, and further including those with added carbides or carbonitrides such as Ti, Ta, and Nb), cermet (for example, those mainly composed of TiC, TiN, and TiCN), ceramics (for example, titanium carbide, silicon carbide, silicon nitride, aluminum nitride, and aluminum oxide), cBN sintered body, or diamond sintered body.
[0038] (2) Shape The shape of the base material is not particularly restricted as long as it is a shape that can be used as a cutting tool; examples include the shapes of end mills, drills, and inserts.
[0039] 4.Measurement method The average thickness of each layer is measured as follows:
[0040] (1) Average thickness of the lower and upper layers 1)Measurement means The overall average thickness of the laminated structural layers constituting the coating layer, as well as the average thickness of other layers, can be determined by observing a longitudinal section (in the case of an insert, a section perpendicular to the surface of the substrate when minute irregularities on the substrate surface are ignored and it is treated as a flat surface; in the case of a shaft tool such as a drill, a section perpendicular to the shaft) using an energy dispersive X-ray spectrometer (EDS) attached to a scanning electron microscope (SEM) or transmission electron microscope (TEM) (hereinafter referred to as the measurement means).
[0041] 2) Surface of the substrate The W count value is determined by line analysis using a measurement method. Five rectangular observation fields are set up, with the length in the vertical direction (thickness direction of the coating layer) encompassing the entire coating layer, and the horizontal direction (parallel to the substrate surface, which is tentatively determined by the difference in density observed from electron microscope observations) being 2 μm. Preferably, each observation field is separated by 3 μm or more from the direction parallel to the tentatively determined substrate surface. In each observation field, line analysis is performed at 10 or more points in the horizontal direction at 0.1 μm intervals and in the vertical direction at 1 nm intervals, from the substrate toward the surface of the coating layer. In each line analysis, the position where the W count value does not decrease further (W minimum position) is determined. Based on the tentatively determined substrate surface, the mean squares method is used to determine the average straight line to this W minimum position, and this is considered the substrate surface thereafter. The direction perpendicular to this surface is defined as the thickness direction of the coating layer.
[0042] 3) Interface between the lower layer and the upper layer In step 2) above, the line analysis results used to determine the substrate surface are analyzed within the observation field set for determining the substrate surface, and the position closest to the substrate surface where the Al count value does not decrease further (the Al minimum position) is determined. Then, relative to this Al minimum position, an average straight line parallel to the substrate surface is determined using the mean squares method, and this is considered to be the interface between the lower layer and the upper layer. The line analysis is then performed up to the upper end of the upper layer to determine the upper end of the upper layer.
[0043] 4) Average thickness of each layer Based on the substrate surface, the interface between the lower layer and the upper layer, and the upper edge of the upper layer, as determined in 2) and 3) above, the average thickness of each layer is calculated.
[0044] (2) Confirmation of epitaxial growth For the observation field, electron backscatter diffraction (EBSD) images are acquired for the longitudinal cross-section of the coating layer in each of the five observation fields (pixel shape is a regular hexagon, pixel spacing is 5-10 nm). At this time, boundaries with an orientation difference of 5° or more are considered grain boundaries, and the regions enclosed by these grain boundaries are considered to be crystal grains.
[0045] Of the crystal grains obtained as described above, those that cross the interface between the lower and upper layers, as determined previously, are defined as epitaxially grown crystal grains. When N is the total number of epitaxially grown crystal grains, and αi (μm) is the length across the 1.5 μm interface by each epitaxially grown crystal grain (i), the proportion occupied by the epitaxially grown portion in each of the five observed fields is calculated using equation (1). The average of these calculated values is taken as the proportion of epitaxially grown crystal grains from the lower layer to the upper layer.
[0046]
number
[0047] Furthermore, in the five observation fields, the distance hi in the thickness direction of the coating layer between the interface and the point closest to the coating layer surface on each epitaxially grown crystal grain (i) was measured. This was performed for all epitaxially grown crystal grains in the measured region, and the amount of protrusion onto the coating layer surface was calculated using equation (2).
[0048]
number
[0049] (5) Average composition The average composition is measured as follows:
[0050] (5-1) Lower layer For the five observation fields mentioned above, the component composition is measured at five locations within each observation field using energy-dispersive X-ray spectroscopy (EDS) with a scanning electron microscope (SEM) or TEM (TEM) (with an observation magnification of 50,000 to 500,000 times). The average composition is then calculated from the average value of these measurements.
[0051] (5-2) Upper layer In the thickness direction of the coating layer, at least 4 line analyses are performed for each observation field of view by EDS attached to TEM and SEM at an interval of 0.4 μm in the direction parallel to the substrate surface (the beam diameter of the line analysis can be exemplified as 0.5 nm, and the interval between observation points in the thickness direction of the coating layer can be exemplified as 0.5 nm). On all analysis lines, the chemical composition at the maximum point of Al element and the maximum point of Ti element in each layer per line analysis is measured in at least 5 layers (5 positions), and the average composition of each layer is obtained by averaging all the measurement results.
[0052] 5. Manufacturing Method The coating layer of the present embodiment is produced, for example, by the following PVD method. That is, the inside of an arc ion plating apparatus (hereinafter referred to as a film forming apparatus) is set to a nitrogen atmosphere, For forming the A-th layer, Al 1-a-b Ti a X b Y c N (X is Ta and / or Nb, Y is Si and / or B, and the average values satisfy 0.40<a<0.70, 0<b<0.20, 0.00≦c<0.05 respectively), the target represented by this formula (AlTiXY alloy target), For forming the B-th layer, Ti 1-d-e Si d Z e N (Z is at least one selected from the group consisting of Ta, Nb and B, and the average values satisfy 0.15<d≦0.40, 0.00≦e≦0.20 respectively), the target of this formula (TiSiZ alloy target), Further, a Ti target and a Cr target for bombardment treatment and underlayer formation, a means for performing Ar bombardment treatment on the lower layer, and a Ti target for surface layer formation are prepared as necessary.
[0053] Then, arc discharges are sequentially generated between these targets and the anode electrode to deposit a base layer, A layer, B layer, and surface layer of a predetermined average thickness. Specifically, bombardment is performed in a vacuum atmosphere using a selective Ti or Cr target, then the Ti or Cr target is selectively energized in a nitrogen atmosphere to form the base layer, the lower layer consisting of A layer is deposited by energizing only the AlTiXY alloy target in a nitrogen atmosphere, then the upper layer is deposited by energizing the TiSiZ alloy target, and after depositing the upper layer consisting of a predetermined number of layers, the surface layer is selectively coated by energizing only the Ti alloy or Cr alloy target to deposit the film.
[0054] For the deposition of the first compound in the lower layer, the bias voltage is set to a range of -40 to -100V, the arc current is set to 150A or less to suppress droplet formation in the lower layer and promote epitaxial growth, high-melting-point elements such as Ta and Nb are added to the target, and Ar bombardment is performed on the lower layer as needed. Furthermore, for the deposition of the first and second compounds in the upper layer, the arc current during discharge is adjusted to a range of 80 to 150A, and the bias voltage to a range of -40 to -200V, respectively. [Examples]
[0055] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0056] (1) Manufacturing of the substrate As raw material powders, WC powder, TiC powder, VC powder, TaC powder, NbC powder, Cr3C2 powder, and Co powder were prepared and blended as shown in Table 1. Then, wax was added and the mixture was ball-milled in acetone for 24 hours, dried under reduced pressure, and then press-molded into compacts of a predetermined shape at a pressure of 98 MPa.
[0057] This compacted powder was vacuum sintered to form a sintered round bar for base formation with a diameter of 6 mm. Furthermore, end mill bases 1 to 4 made of WC-based cemented carbide were manufactured from the aforementioned sintered round bar by grinding, with four square cutting edges measuring 6 mm in diameter and 13 mm in length. Then, each of these substrates 1 to 4 was ultrasonically cleaned in acetone and dried.
[0058] (2) Manufacturing of the coating layer A substrate was mounted along the outer circumference of the rotating table of the film deposition apparatus at a predetermined radial distance from the central axis. A target (cathode electrode) of an AlTiXY alloy of a predetermined composition for layer A deposition, a target of a TiSiZ alloy of a predetermined composition for layer B deposition, and further, targets of Ti and Cr for underlayer formation, and a Ti target for surface layer formation were arranged.
[0059] For each of the substrates 1 to 4, a coating layer was formed in the following manner after bombardment to clean the substrate surface.
[0060] 1) Film formation of the underlying layer In some embodiments, the underlayer was formed by the following procedure. As shown in Table 8, the inside of the film deposition apparatus was kept under a nitrogen atmosphere for the deposition of the underlayer, the temperature of the substrate rotating on a rotary table was maintained at 450 or 600°C, a DC bias voltage of -20 or -100V was applied, and an arc discharge was generated between the Ti or Cr target and the anode electrode to deposit an underlayer composed of TiN or CrN on the surface of the substrate.
[0061] 2) Film formation of the lower layer A first compound constituting the lower layer, layer A, is deposited on the substrate surface or the surface of the underlying layer. Nitrogen gas is introduced as a reaction gas into the deposition apparatus to create a nitrogen atmosphere of 2.0 to 5.5 Pa, as shown in Table 2. The temperature of the substrate rotating on the rotary table is maintained at 450 to 500°C, and a DC bias voltage of -30 to -100V is applied. An arc discharge is generated between the target (see Table 2) of the AlTiXY alloy target alloy corresponding to the composition of the first compound constituting layer A to be deposited and the anode electrode, thereby depositing the lower layer. In some embodiments, Ar is ionized, and a bias voltage of -200 to -400V is applied to perform bombardment on the lower layer.
[0062] 2) Film formation of the upper layer To deposit a laminated film consisting of alternating layers of B and A, the deposition of the upper layer began with the B layer. The nitrogen gas atmosphere in the deposition apparatus was set to 2.0-5.5 Pa, and an arc discharge was generated between the TiSiZ alloy target (see Table 4) corresponding to the composition of the second compound constituting the B layer and the anode electrode to deposit the B layer. The nitrogen atmosphere pressure, substrate temperature, and bias voltage were as shown in Table 4.
[0063] Next, to deposit layer A, the film was deposited by generating an arc discharge between the AlTiXY alloy (see Table 2) and the anode electrode. The nitrogen atmosphere pressure, substrate temperature, and bias voltage are shown in Table 3. The film deposition process was repeated so that a predetermined number of stacked units, in which layers B and A were alternately stacked, were formed.
[0064] 5) Formation of the surface layer In some embodiments, the upper layer was formed by the following procedure. Nitrogen gas was introduced as a reaction gas into the film deposition apparatus, and as shown in Table 8, the pressure of the nitrogen atmosphere for upper layer deposition was set to 4.0 Pa, the temperature of the substrate rotating on the rotary table was maintained at 500°C, and a bias voltage of -75V was applied. An arc discharge was generated between the Ti target and the anode electrode corresponding to the composition of the upper layer to be deposited, and a surface layer composed of TiN was deposited.
[0065] Following the above procedure, surface-coated end mills 1 to 9 (referred to as Examples 1 to 9) of the examples described in Tables 9 and 11 were manufactured.
[0066] (3) Comparative Example For comparison, each of the substrates 1 to 4 was ultrasonically cleaned in acetone, dried, and mounted along the outer circumference at a predetermined radial distance from the central axis on the rotary table of the film deposition apparatus. Without bombardment, the surface-coated end mills 1' to 9' of the comparative examples shown in Tables 10 and 12 (hereinafter referred to as Comparative Examples 1' to 9') were manufactured using the targets shown in Tables 5 to 7 and the film deposition conditions 1' to 9' in Tables 5 to 7 (the number of first and second layers was the same). In addition, some of the comparative examples had the underlayer and / or surface layer deposited using the targets and film deposition conditions described in Table 8.
[0067] For Examples 1-9 and Comparative Examples 1'-9', the average composition and average thickness were calculated using the method described above.
[0068] [Table 1]
[0069] [Table 2]
[0070] In the "Presence or Absence of Ar Bombardment Treatment on Lower Layers" column of Table 2, "-" indicates that bombardment treatment was not performed, and "○" indicates that it was performed.
[0071] [Table 3]
[0072] [Table 4]
[0073] [Table 5]
[0074] As indicated by the "-" in the "Presence or Absence of Ar Bombardment Treatment on the Lower Layer" column in Table 5, Ar bombardment treatment was not performed on the lower layer in any of the comparative examples.
[0075] [Table 6]
[0076] [Table 7]
[0077] The target compositions in Tables 2-7 are expressed such that the sum of the atomic ratios of each atom equals 1.00.
[0078] [Table 8]
[0079] [Table 9]
[0080] [Table 10]
[0081] [Table 11]
[0082] [Table 12]
[0083] In Tables 11 and 12, "○" indicates satisfaction, and "×" indicates dissatisfaction.
[0084] Next, for Examples 1 to 9 and Comparative Examples 1' to 9', wet continuous cutting tests were performed with each component fixed to a milling chuck using a fixing jig, under cutting condition 1 for Ti-based alloys, cutting condition 2 for stainless steel, and cutting condition 3 for Ni-based alloys, respectively, and the flank wear width of the cutting edge was measured.
[0085] <Cutting conditions 1> Workpiece: Ti-6Al-4V plate with dimensions of 250mm x 100mm and a thickness of 60mm. Cutting speed: 100 m / min. Rotation speed: 5500 min -1 . Cutting depth: ae 0.3 mm, ap 6 mm Feed rate (per tooth): 0.08 mm / tooth Cutting length: 200 m Cutting fluid: Water-soluble coolant
[0086] <Cutting conditions 2> Workpiece: SUS304 stainless steel plate with dimensions of 250mm x 150mm and a thickness of 60mm. Cutting speed: 100 m / min. Rotation speed: 5500 min -1 . Cutting depth: ae 0.3 mm, ap 6 mm Feed rate (per tooth): 0.08 mm / tooth Cutting length: 300 m Cutting fluid: Water-soluble coolant
[0087] <Cutting conditions 3> Work material: Ni-based heat-resistant alloy plate (Cr18 mass%-Fe18 mass%-Nb5 mass%-Mo3 mass%-Ti1 mass%-Al0.5 mass%-Ni remainder) with planar dimensions of 50 mm x 150 mm and thickness of 250 mm. Cutting speed: 100m / min. Depth of cut: AP 2.4mm, ae 0.3mm Cutting length: 50m Feed rate: 0.05mm / tooth Cutting fluid: Water-soluble coolant
[0088] Tables 13-15 show the results of these three types of cutting tests.
[0089] [Table 13]
[0090] In Table 13, the (*) in the "Comparative Example" column indicates the cutting distance (m) until the end of service life was reached, as the tool reached its end of service life before reaching a cutting length of 200m due to reasons such as delamination, welding, chipping, or wear.
[0091] [Table 14]
[0092] [Table 15]
[0093] The results shown in Tables 13-15 demonstrate that Examples 1-9 all exhibit excellent durability, even during high-speed cutting of Ti-based alloys, stainless steel, and Ni-based alloys, without peeling, welding, chipping, or wear of the coating layer. In contrast, in Comparative Examples 1' to 9', regardless of whether the machining was of Ti-based alloys, stainless steel, or Ni-based alloys at high speed, the thermal and mechanical loads during machining caused peeling, welding, chipping, and wear of the coating layer, resulting in a short tool life. [Explanation of Symbols]
[0094] 1 Base 2 Covering layer 3 Lower layer 4 Upper layer 5 A layer 6 B layer 7 Layer Units 8. Interface between the lower layer and the upper layer 9. Epitaxially grown crystal grains 10 Overhang amount 11 non-epitaxially grown crystal grains
Claims
[Claim 1] A surface-coated cutting tool having a substrate and a coating layer, The coating layer includes a lower layer and an upper layer. The lower layer has layer A, and the upper layer is a laminate with layer B on the substrate side and layer A on layer B as the stacking unit. The aforementioned upper layer and lower layer both have an average thickness of 0.5 to 3.5 μm, and the combined average thickness of both layers is 1.0 to 5.0 μm. The aforementioned layer A is given by formula: Al a Ti 1-a-b X b Y c It consists of a first compound represented by N (where X is Ta and / or Nb, and Y is Si and / or B, with average values of 0.40 < a < 0.70, 0.00 ≤ b < 0.20, and 0.00 ≤ c < 0.05), The aforementioned layer B is given by equation: Ti 1-d-e Si d Z e It consists of a second compound represented by N (where Z is at least one selected from the group consisting of Ta, Nb, and B, with average values of 0.15 < d ≤ 0.40 and 0.00 ≤ e ≤ 0.20 for each), In the longitudinal cross-section of the coating layer, among the crystal grains that traverse the interface between the lower layer and the upper layer, the proportion of crystal grains that have grown epitaxially from the lower layer to the upper layer is 70% or more, and when the average thickness of the upper layer is L and the average amount of the protrusion of the epitaxially grown crystal grains from the interface towards the upper layer is H (μm), then 0.05 × L (μm) < H < 0.50 (μm). A surface-coated cutting tool characterized by the following features.
Citation Information
Patent Citations
Hard film
JP2007056304A
Coated Cutting Tools
JP2023531295A